Instrumental political support: bringing policy preferences back into explanations of EU support. Issue 4 (4th July 2017) - Belot, Céline; Guinaudeau, Isabelle
Abstract: There is a joint development towards Europeanisation of public policies and an increasing visibility and politicisation of European issues in EU member states. In this context, the degree of fit between individuals' policy preferences and European norms could be expected to influence support for the EU: this support might increase when Europeanisation makes the desired policies more likely, and decrease when it hinders these policies. Multilevel analyses of the 2014 wave of the European Election Study confirms the existence of such instrumental support for the EU. The findings demonstrate that this support is shaped by policy preferences on state intervention, immigration, moral issues and environmental protection. The results also show that the impact of these policy preferences is modulated by the level of integration of the designated policy, by the weight of the policy issue in the country and, in some cases, by the level of individual political knowledge.